The Dualism of the Indonesian Labor Market: Between Investment, Wages, and Education Level - Arjuna Wahyu Permana Ajie; Muhammad Anas (STIE Amkop Makassar, 2026)
Labor absorption is a key indicator for assessing an economy’s ability to optimally absorb labor and distribute income in order to improve public welfare and reduce poverty rates. This study aims to estimate the effects of education level (average years of schooling), minimum wage, domestic investment (DDI), and foreign investment (FDI) on formal and informal labor absorption in Indonesia from 2019 to 2024 using panel data regression with a Fixed Effects Model (FEM) approach. The regression results in Model 1 indicate that average years of schooling has a positive effect and the minimum wage has a negative effect on formal labor absorption, while domestic investment and foreign investment do not have a significant effect on formal labor absorption. Meanwhile, in Model 2, it was found that average years of schooling has a negative effect, minimum wage and foreign investment have a positive effect, while domestic investment has no significant effect on informal labor absorption. Therefore, the government is expected to formulate policies focused on improving the quality of education and workforce skills, controlling minimum wage increases in a proportionate manner, and encouraging labor-intensive investment t expand employment in the formal sector in Indonesia.